Benefactions toward Temples in the Ptolemaic Fayum - Wilimowska, Joanna.
The aim of this article is to present all attestations of contributions to temples of various cults in the Fayum oasis under Ptolemaic rule. In antiquity, sacred places were financed in many ways. Endowments were focused especially on temple buildings and have not only religious but also political and socio-economic functions. Thus, patronage of temples may be to some extent treated as euergetism. The majority of the preserved documentation providing evidence of patronage of temples comes from the Fayum. This study provides an updated list of benefactions toward temples in the Fayum and investigates their function and significance in the temples’ life within the broader Ptolemaic society.   doi: http://dx.doi.org/10.5913/jarce.54.2018.a015